Guest Insight Regarding Service Quality in Hotels: An Empirical Study from Bangladesh - Bhowmik, Debasree; Hasan, Shahariar; Nafi, Shohel Md. (Journal of Digital Marketing and Communication, 2024)
The tourism industry is one of the major service sectors expanding rapidly. Hotels play a prime role in delivering service to guests and creating satisfaction. This study aims to measure the guest insight regarding the service quality of star-ranking hotels in Bangladesh. Thus, a quantitative approach was used to conduct the study, and a well-structured, close-ended questionnaire was developed. This study used a five-point Likert scale for collecting data. Statistical tool SPSS 24 was used for data analysis. The analysis of guest insight towards the service quality of star-ranking hotels in Bangladesh shows a positive picture. Key areas such as service quality, food quality, location, and modern facilities receive high satisfaction scores, indicating the hotel's strengths. Safety and security measures are also well-regarded, although in-room security features need enhancement. Employee behavior shows a favorable view, particularly in complaint resolution, though overall service and interaction could improve. Green environment practices are recognized but have growth opportunities, especially in promoting energy-saving initiatives. This study will help to reshape the hotel services in Bangladesh and give direction for more extensive research to identify the segmentation-based hotel service.